Concussion epidemiology in athletes who are deaf or hard-of-hearing compared with athletes who are hearing - Brancaleone, M. P.; Clifton, D. R.; Onate, J. A.; Boucher, L. C. (Clinical Journal of Sport Medicine, 2021)
Objective: To compare the epidemiology of concussion between athletes who are deaf or hard-of-hearing (D/HoH) and athletes who are hearing. Design: Descriptive epidemiology study. Setting: Data were collected from 2 Division III athletic programs. One institution is the world's only university designed to be barrier-free for students who are D/HoH. Participants: Six hundred ninety-three athletes who are D/HoH and 1284 athletes who are hearing were included in this study. Athletes participated in collegiate athletics during the 2012 to 2013 through the 2016 to 2017 academic years. Interventions: Concussion data were provided by the athletic training staff at each institution. Main Outcome Measures: Concussion counts, concussion rate, and injury rate ratios (IRRs) with 95% confidence intervals (95% CIs). Results: Thirty athletes who are D/HoH and 104 athletes who are hearing suffered concussions. Athletes who are hearing had an increased injury rate compared with athletes who are D/HoH for all sports combined (IRR = 1.87, 95% CI, 1.26-2.78). Football athletes who are hearing also had an increased injury rate compared with football athletes who are D/HoH (IRR = 3.30, 95% CI, 1.71-6.37). Concussion rate was higher for male athletes who are hearing than male athletes who are D/HoH (IRR = 2.84, 95% CI, 1.62-4.97). No other significant differences regarding concussion risk were identified. Conclusions: Athletes who are D/HoH in sex-comparable sports may not have a higher rate of concussion than athletes who are hearing. Rate of concussion in football may be greater among athletes who are hearing compared with athletes who are D/HoH.